2008
DOI: 10.1016/j.brainres.2008.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral injection of ghrelin induces Fos expression in the dorsomedial hypothalamic nucleus in rats

Abstract: Peripheral ghrelin has been shown to act as a gut-brain peptide exerting a potent orexigenic effect on food intake. The dorsomedial nucleus of the hypothalamus (DMH) is innervated by projections from other brain areas being part of the network of nuclei controlling energy homeostasis, among others NPY/AgRP-positive fibers arising from the arcuate nucleus (ARC). The aim of the study was to determine if peripherally administered ghrelin affects neuronal activity in the DMH, as assessed by Fos expression. The num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…It has been reported that peripheral administration of ghrelin can induce c-fos expression, a marker of neuronal activation, in the brain (38). In this study, we have also observed an increase of c-fos expression in the brainstem of aged septic rats after combined treatment.…”
Section: Combined Human Ghrelin and Gh Activates Brain Activity In Agsupporting
confidence: 81%
“…It has been reported that peripheral administration of ghrelin can induce c-fos expression, a marker of neuronal activation, in the brain (38). In this study, we have also observed an increase of c-fos expression in the brainstem of aged septic rats after combined treatment.…”
Section: Combined Human Ghrelin and Gh Activates Brain Activity In Agsupporting
confidence: 81%
“…However, Kobelt et al . (2008) did not find any change in c-Fos positive neurons in the NTS after peripheral administration of AG [17]. Unacylated ghrelin (UAG) also occurs in the circulation [13].…”
Section: Introductionmentioning
confidence: 94%
“…While the c-Fos immunolabeling technique can provide information regarding increases in neuronal activity, decreases in activity brought about by membrane hyperpolarization cannot be identified. Indeed, some c-Fos immunolabeling studies have reported that ghrelin does not induce c-Fos in the AP (34) or induces only weak immunolabeling (56) and suggested that AP is not an important site of action within the CNS. The fact that 19% of the neurons modulated by ghrelin in this study were hyperpolarized suggests that previous studies have underestimated the ability of AP to detect circulating ghrelin and communicate this information to other sites involved in regulation of energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of ghrelin into the NTS or nearby areas stimulated feeding at doses below the threshold required for forebrain injections (17). Many investigators observe that peripheral administration of ghrelin also caused increases in caudal brain stem c-Fos immunoreactivity (24,37,38,56), although such changes have not been reported in all studies (34). Moreover, recent observations by Gilg and Lutz (21) have convincingly demonstrated a role for AP in ghrelin-mediated feeding.…”
mentioning
confidence: 99%